Legal Consequences of the Auction of the Auction Object Related to the Beneficial Owner of the Auction Object Over the Buyer - Salsabila, Amira Choirunnisa; Anshari, Tunggul; Widhiawati, Dyah (International Journal of Business, Law, and Education, 2025)
A competitive auction consists of a public sale managed by a second manager, where sellers and buyers exchange assets as specified in mutual documents. According to the provisions of Article 38(c) of the Financial Regulation No. 4662; these officials cannot purchase goods directly or indirectly in their presence, in accordance with the Secondary Officials Law No. 189/PMK.06/2017. However, the fact that the legislation does not specify specific conditions regarding the concept of "direct or indirect purchase" causes confusion. This ambiguity raises concerns about abuses such as buy-side consultants participating in money laundering (TPPU). This study examines two important issues: the limitations of the term "buyer" in Section 38(c) and the legal benefits provided to employees associated with the buyer-owner. Remain loyal to the judicial system, use law and techniques to analyse the interpretation of the law. The study ends with the clarification of the scope of the ban and the investigation of the legal consequences of non-compliance with the ban. These findings can form the basis for recommendations to the relevant authorities on resolving legal issues and preventing abuse of the auction process, complying with legislation and ethical rules